Design and experimental validation of improved grapevine burying machine - Yang, Shuming; She, Huiyan; Yang, Shuchuan; Zhu, Xuejun; Chen, Yun; Li, Jinhai; Li, Maoqiang (International Journal of Agricultural and Biological Engineering, 2018)
In order to address the low soil breaking rate, poor soil covering performance, and low working efficiency of the existing 3MT-1.8 and PMT-75 grapevine burying machines, two types of improved burying machines, namely the 3MTLJ-1.8 and 3MTXP-1.8, were developed in consideration of the local Ningxia soil conditions. Field experimental results indicated that the soil breaking rate of the 3MTLJ-1.8 machine was 71.44%, and its soil sampling volume increased by approximately 30% compared to that of the 3MT-1.8 machine. It was verified that the self-developed 3MTLJ-1.8 machine can be used in the southern regions of Ningxia. Furthermore, the soil sampling volume of the 3MTXP-1.8 burying machine was 0.24 m3/m, and its soil breaking rate increased by more than 41.42% compared to the standard required volume. The 3MTXP-1.8 machine can be used in the northern areas of Ningxia, where the soil hardness is higher. The results can provide a reference for the development and popularization of grapevine burying machines in Ningxia.Keywords: grapevine burying machine, improvement, soil sampling performance, soil covering performance, soil breaking rateDOI: 10.25165/j.ijabe.20181102.2927Citation: Yang S M, She H Y, Yang S C, Zhu X J, Chen Y, Li J H, et al. Design and experimental validation of improved grapevine burying machine. Int J Agric & Biol Eng, 2018; 11(2): 95–100.